Interference by ASEAN: Are there double standards? - Tan, Aaron Kai Wen (Nanyang Technological University, 2023)
Although many have written extensively about the ASEAN’s non-interference principle and its role in influencing intra-ASEAN relations, few, if any, have focused their attention on instances of disparate application of the principle and the causes for it. By drawing on a comparison between ASEAN’s responses towards the 2014 Thailand coup and the 2021 Myanmar coup, this paper seeks to demonstrate that elements of dissonance and practice contradictory of the principle exist within the Association. In this paper, I argue that the first step towards understanding these inconsistencies in organisational behaviour must be through the examination of social dynamic factors, specifically, the reputation and competence of the juntas. In deciding an initial response to the coup, member states will be guided by the historical patterns of behaviour of the junta and subjective feelings about its intentions and capabilities. As the coup enters into a later stage, the deciding variable of the non-interference principle shifts to whether the junta is able to demonstrate sufficient competence in a way that protects ASEAN’s strategic interests.